The Impact of Accounting Standards on Earnings Quality, Earnings Management, and Income Smoothing Before and After the Implementation of Accounting Standards in Iran - Hajibagloo, Mohsen; Nakhaei, Habibollah; Shoorvarzi, Mohammad Reza; Noori Topkanloo, Zahra (Business, Marketing, and Finance Open, 2025)
Since financial statements are among the most critical sources of information for decision-makers, it is essential to comply with accounting standards in their preparation. These standards serve as a benchmark for the quality of information contained in financial statements. Following the mandatory implementation of accounting standards approved by the Audit Organization in Iran, the question arises as to whether these standards have improved the quality of accounting information. Therefore, this study aims to examine the impact of accounting standards on earnings quality, earnings management, and income smoothing before and after the implementation of accounting standards in Iran. The research follows a fundamental-experimental approach. The statistical population of this study comprises all companies listed on the Tehran Stock Exchange, and a systematic elimination sampling method was used to select the sample. The sample size was 61 firms. The financial data of these companies were examined over a 31-year period (1992–2022). To collect the necessary data for hypothesis testing, financial data of the selected companies were extracted using Rahavard Novin software and the Iranian Securities and Exchange Organization's databases. A multiple linear regression model was employed to test the hypotheses. In the statistical analysis, regression based on panel data was used to analyze the research hypotheses, and the data analysis was conducted using Eviews and Excel software. According to the results, earnings quality did not have a significant relationship with earnings management among companies listed on the Tehran Stock Exchange before and after the implementation of accounting standards. However, earnings quality was significantly related to income smoothing among these companies before and after the implementation of accounting standards. Additionally, income smoothing had a significant relationship with earnings management among companies listed on the Tehran Stock Exchange before and after the implementation of accounting standards.